Effects of nitrogen/bismuth-doping on the photocatalyst composite of carbon dots/titanium dioxide nanoparticles (CDs/TNP) for enhanced visible light-driven removal of diclofenac - Hui, K.C. (NLM (Medline), 2022)
The present work demonstrates the coupling of titanium dioxide, TiO2 nanoparticles (TNP) with N-doped, Bi-doped, and N-Bi co-doped rice husk-derived carbon dots (CDs) via a facile dispersion method, forming respective photocatalyst composites of CDs/TNP, N-CDs/TNP, Bi-CDs/TNP and N-Bi-CDs/TNP. Characterization analyzes verified the successful incorporation of respective CDs samples into TNP, forming photocatalyst composite with narrowed band gap and quenched photoluminescence intensity. Photocatalytic activity of TNP and the respective composites was investigated for photodegradation of diclofenac (DCF) under both simulated sunlight and natural sunlight irradiation. The as-prepared N-Bi-CDs/TNP composite showed the best photocatalytic performance among all composites, able to completely degrade 5Â ppm of DCF within 60Â min and 180Â min under both types of visible light irradiation, respectively. The N-Bi-CDs/TNP composite also showed a TOC removal efficiency up to 87.63. N-Bi-CDs, worked as photosensitizer and electron reservoir, contributed to the outstanding photocatalytic activity of N-Bi-CDs/TNP, whereby the recombination was prolonged and light absorption was shifted towards the visible light region. Furthermore, the composite of N-Bi-CDs/TNP also demonstrated good stability and reusability over repeated degradation cycles. The photodegradation of DCF resulted into several intermediates, which were identified from LC-MS analysis. The present work could provide an insight on the application of heteroatoms doped and co-doped carbon dots in semiconductor oxide as high performance photocatalysts. Copyright Â© 2021 Elsevier Ltd. All rights reserved.